Pengaruh Tingkat Marjin Murabahah Terhadap Financing To Deposit Ratio dan Non Performing Financing Pada Bank Syariah di Indonesia Periode 2010-2012 - Saputro, Nareswari; Mawardi, Imron (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
This study aims to determine the effect of the murabahah margin rate to Financing to Deposit Ratio and Non Performing Financing on Indonesian Sharia Banks in the period 2010-2012. This study uses quantitative approach by using path analysis with three kinds of variables, which are murabahah margin rate as an exogenous variable, Financing to Deposit Ratio as an intervening endogenous variables and Non Performing Financing as an endogenous variable. The Sharia Banking industry is used as sample in this study, which consist of Sharia Comercial Banks (BUS) and Sharia Business Unit of a Conventional Bank (UUS). Furthermore, this study uses secondary data which conducted by collecting monthly financial statements for three years.The results showed that murabahah margin rate has significantly negative effect to Financing to Deposit Ratio (FDR) of Sharia Banking in Indonesia. Meanwhile, murabahah margin rate has significantly positive effect to Non Performing Financing (NPF). It also happens to the effects of Financing to Deposit Ratio (FDR) to Non Performing Financing (NPF) of Sharia Banks in Indonesia period 2010-2012.